SOSIALISASI PENINGKATAN KESELAMATAN PERLINTASAN SEBIDANG KEPADA PARA PEGIAT MEDIA SOSIAL DI TULUNGAGUNG (JPMPPI (Jurnal Pengabdian Masyarakat), 2022)
Train accidents often grace the pages of mainstream media and social media. There are several reasons for the high number of accidents at this level crossing. According to the Public Relations Manager of PT KAI (Persero) Daop 7 Madiun, Ixfan Hendriwintoko, this accident indicated that the driver did not comply with the signs and regulations that were available (Surabaya.liputan6.com, 2020). Socialization through social media is the most effective step to convey information. Including the rules of railway. However, not all accounts have high affordability to netizens. Accounts with many followers and subscribers owned by social media activists have high affordability. Traffic safety will continue to be an important issue. It has even become one of the targets of the Sustainable Development Goals (SDGs). For this reason, increasing understanding of the rules is an effective solution to reduce accidents, especially at level crossings. One of them is through the Socialization of Increased Level Crossing Safety to Social Media Activists in Tulungagung. From the evaluation results showed an increase in the average value of the post test to the pre test. Paired T-test results show a significance value (p-value) or Sig. (2-tailed) is less than (0.05) or 0.000. This means that the average test scores are different before and after socialization. In conclusion, socialization has an impact on the level of understanding of the participants